Social solidarity collaborative action for equality in education and poverty reduction post conflict and disaster in Aceh, Indonesia - Alfiatunnur, Alfiatunnur; Hardy, Mike; Contractor, Sariya Cheruvallil; Nazliati, Nazliati; Nashriyah, Nashriyah (Universitas Islam Negeri Ar-Raniry, 2024)
Education is a road map of the nation's development, conveying the value of society and the purpose of the nation, where both formulas are invested in curricula. Poverty is a real challenge for education development, and it can be considered a direct result of collective leadership failure in the provision of both quality education and welfare support. This study examines a social collaborative action served by the community to provide an equal education for vulnerable children, a part of a solidarity coping strategy for poverty reduction. The samples of this qualitative approach study are social workers from Yayasan Kesejahteraan Masyarakat Aceh (Yakesma/Aceh Welfare Foundation), who initiates a social collaborative action, involving society, educators, and other stakeholders in various role-play. This study proves that combined actions of social workers, educators, and society in providing equal education to children from lower-income families, beggars, and sexual violence, have given a significant impact on the children and families, giving more access the children to have proper education, formal and non-formal education, financial support through a foster parent program, and provides a role substitute of parents. This collaborative program has created a parthway to a proverty reducation in Aceh, Indonesia. A part of the institution’s main goal to support the vulnerable children in Aceh.